Prevalência de historia familiar positiva em portadores de síndromes degenerativas demenciantes - Souza, Marilda Aparecida do Nascimento (2016)
INTRODUCTION: The main risks factors of dementia are: aging, medical comorbidities and genetic risk. Genetic factors are very important in the investigation of dementia. A positive family history and genetic factors associated can influence the age of onset of the disease. OBJECTIVES: To investigate the prevalence of family history in dementiating degenerative syndromes. To analyze the cognitive and functional performance of these patients to determine whether the positive FH is related to the early onset of the disease, to assess the prevalence of positive FH by dementia subtype, to compare the profile sociodemographic patients with degenerative dementia with family history and no family history and observe which group had more severe dementia. METHODS: This is a cross-sectional study, conducted in the memory clinic of a university hospital in Central Brazil . Were assigned 483 patients with a diagnosis of dementia, from May 2015 to May 2016. This study evaluated the sociodemographic variables, pre- existing diseases and FH of dementia, through a semi-structured interview. To analyze the cognitive level and functional capacity was used the Mini-mental state examination - MMSE and Pfeffer Questionnaire. The Clinical Dementia Rating - CDR was used to assess the severity of dementia. RESULTS: Of the 483 selected participants, 63.8% were women; the average age at evaluation was 74 years, most with low education (32.7%). We found that 45.5% of patients have an affected relative, mostly among simblings, and the age of onset of dementia is lower in people who have positive HF. Positive FH was greater in Huntington's disease 88.8%, followed by Semantic Dementia (66.7%) and primary progressive aphasia (66.7%). CONCLUSION: Family history proved very common in all types of dementia in our sample, mainly in Huntington's disease, followed by frontotemporal lobar degenerations.